Fatigue resistance of Y-TZP/porcelain crowns is not influenced by the conditioning of the intaglio surface - Anami, L. C. [UNESP]; Lima, J. M.C. [UNESP]; Valandro, L. F.; Kleverlaan, C. J.; Feilzer, A. J.; Bottino, M. A. [UNESP] (Operative Dentistry, 2016)
Objectives: The objective of this study was to investigate the effects of treatments of the intaglio surface of Y-TZP frameworks and luting agents on the fatigue resistance of allceramic crowns. Methods: A research design was chosen that attempted to reduce the likelihood of Hertzian cracking and to increase the probability of fracture initiation at the intaglio surface of the framework. Ninety identical preparations were machined in a dentin-like epoxy composite. Each preparation was restored with a YTZP framework made by a CAD/CAM system and veneered using feldspathic ceramic. Prior to cementation the intaglio surface of the ceramic was treated using one of four treatments: 1) cleaning with isopropyl alcohol; 2) application of an overglaze; 3) sandblasting with 125 lm aluminum oxide powder; and 4) sandblasting with 30 lm silica powder (CJ). One of three luting cements were used: 1) zinc phosphate; 2) glass ionomer; and 3) adhesive resin cement (PN). All three cements were tested against frameworks that were alcohol cleaned. Only the PN cements were tested against frameworks that had been sandblasted or glazed. Altogether, six groups of 15 specimens each were tested. Fatigue resistance was evaluated using stepwise loads at 1.4 Hz until failure: 5000 cycles at maximum load of 200 N, followed by 10,000 cycles at maximum loads of 800, 1000, 1200, and 1400 N. The cement thickness and failure modes were analyzed using a stereomicroscope and scanning electron microscopy. The results were analyzed using the Kaplan-Meier and Mantel-Cox log rank tests (5%), a one-way analysis of variance, Tukey multiple comparison test, and Weibull nonparametric test. Results: The predominant failure mode was chipping of the veneer. The crowns cemented with the adhesive resin cement exhibited chipping failure at higher mean loads than did crowns cemented with cements that usually do not bond strongly with dentin. When the adhesive cement was used, glazing and sandblasting intaglio framework surface treatments exhibited lower mean loads at chipping than did crowns whose intaglio surface was only cleaned with alcohol. Weibull analysis indicated that all specimens had a high ratio of late-to-early failures. Conclusions: The fatigue experiment produced a pattern of failures that is very similar to that observed in clinical trials of Y-TZP crowns that are veneered with feldspathic porcelain. Crowns cemented with an adhesive resin cement exhibited chipping at a significantly higher mean load than those cemented with luting cements that do not usually form strong bonds with dentin. When cemented with adhesive resin cement, glazing or sandblasting the intaglio surface of the framework significantly reduced the mean fatigue loads at which chipping of veneers occurred, as compared to crowns whose intaglio surface had only been cleaned with alcohol. For this cement glazing or sandblasting the intaglio surface of the crown is not recommended.